2018
DOI: 10.1027/1614-0001/a000253
|View full text |Cite
|
Sign up to set email alerts
|

Militant Extremist Mindset and the Assessment of Radicalization in the General Population

Abstract: Abstract. This paper presents new data and reviews the available evidence pointing to the existence of three main ingredients of militant extremist mindset (MEM). Three different methods of item development identified factors that we have labeled Nastiness, Grudge, and Excuse. In other words, there are in our midst nasty people who are more prepared than others to accept, approve, or even advocate the use of violence. When such people feel a grudge, in that they see somebody as threatening to themselves (or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…Studies have indicated that grievances derived from perceptions of deprivation can become particularly powerful drivers of (violent) political mobilization when they coincide with societal fault lines—when an individual experiences a lack of political representation or socioeconomic opportunity because they belong to a marginalized societal group, for instance (Gurr, 2011; Moghaddam, 2005). Relatedly, we also considered whether individuals felt a strong sense of identification with victims of perceived injustice (e.g., by witnessing the suffering of coreligionists) (Sageman, 2008), felt a marked sense of in‐group threat (Stankov et al., 2018), or had lost trust in the (fair) functioning of society and its institutions (Bhui et al., 2012).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Studies have indicated that grievances derived from perceptions of deprivation can become particularly powerful drivers of (violent) political mobilization when they coincide with societal fault lines—when an individual experiences a lack of political representation or socioeconomic opportunity because they belong to a marginalized societal group, for instance (Gurr, 2011; Moghaddam, 2005). Relatedly, we also considered whether individuals felt a strong sense of identification with victims of perceived injustice (e.g., by witnessing the suffering of coreligionists) (Sageman, 2008), felt a marked sense of in‐group threat (Stankov et al., 2018), or had lost trust in the (fair) functioning of society and its institutions (Bhui et al., 2012).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Saucier relied on the documentary materials of selected extremist groups that were active over the past 150 years in seven world regions (Saucier et al, 2009). Similar to Saucier, Knežević also deployed a conceptual analysis of terrorist texts, but supplemented this extensively with psychological and literary analyses of terrorists' behavior (see Stankov et al, 2018).…”
Section: Components Of Militant Extremist Mindsetmentioning
confidence: 99%
“…In our previous work, when searching through a variety of sources, we identified several themes characteristic of MEM (16 in Saucier et al, 2009;20 in Stankov et al, 2018). These themes, at the same time, reflected information processing styles and motivational drives that could be ascribed to closed-minded individuals, such as Manicheism (black and white worldview; either/or attitude), puritanism, inability to decenter (difficulty in taking another group's perspective), antimodernism and antidemocratism (Stankov et al, 2018), or glorifying the past while believing that modernity is disastrous (Saucier et al, 2009). For these conceptual reasons, as well as our previous findings and the recent contributions of other research groups on the relationships between RWA and MEM components (Vukcevic-Markovic et al, 2021), we expect significant correlations between MEM and the aforementioned dispositional constructs that could be regarded as manifestations of closedmindedness.…”
Section: Closed-mindedness and Memmentioning
confidence: 99%
“…The mind-set captured by these three factors has been labeled Militant Extremist Mind-Set (MEM). It is important to note that slight variations of the three-factor model of MEM (Stankov, Knežević, Saucier, Radovic, & Milovanovic, 2018) suggest that the factor labeled Divine Power can be seen as a part of a broader tendency to excessive idealization related to the chosen political goal. Thus, utopian ideals instead of purity of Divine presence can accommodate MEM groups with an atheistic orientation.…”
Section: Militant Extremist Mind-set (Mem)mentioning
confidence: 99%